Biotechniques: Theory and Practice - Rana S V S; RANA (S V S) (Meerut Rastogi Publications, 2019)
CONTENTS: 1. Assay Methods; 2. Cell and Tissue Culture; 3. Basic Requirements in a Biological Laboratory; 4. Fixation; 5. Histological Methods; 6. Microscopy; 7. Centrifugation; 8. Spectrophotometry; 9. Mass Spectrometry; 10. Electron Spin Resonance and Nuclear Magnetic Resonance Spectroscopy; 11. X-Ray Diffraction; 12. Chromatography; 13. Electrophoresis Instrumentation; 14. Polymerase Chain Reaction (PCR); 15. Immunodiagnostic Methods; 16.Radio-isotopes Techniques; 17. Electrochemical Techniques & Biosensors; 18. Methods of Environmental Analysis; 19. Air Pollution Analysis; 20. Monitoring of Ambient Air Pollution; 21. Water Pollution Analysis; 22. Soil Pollution and Pesticide Analysis; 23. Noise Pollution Measurement; 24. Applications of Computer in Modern Biology; 25. Perfusion, Organ Ablations / Surgical Techniques; 26. Management of Laboratory Animals; 27. Biostatistics; 28. Preparation of Reagents, Stains and Buffers; 29. Hazardous Laboratory Materials/Chemicals; Suggested Further Readings
Keywords: Biotechniques; Biology